You : a novel - Kepnes, Caroline, 1976- (New York : Atria/Emily Bestler Books, 2014)
When aspiring writer Guinevere Beck strides into the East Village bookstore where Joe works, he's instantly smitten. And she's perfect for him, but there's more to Joe than Beck realizes, and much more to Beck than her perfect facade. Their mutual obsession quickly spirals into a whirlwind of deadly consequences.
Keywords: Bookstores -- Fiction; Bookstores -- Employees -- Fiction; Romance-language fiction; Suspense fiction; Romantic suspense fiction